Stakeholder perceptions on scaling-up community-led interventions for prevention and control of non-communicable diseases in Bangladesh: a qualitative study - Kohenour Akter; Abdul Kuddus; Tasnova Jeny; Tasmin Nahar; Sanjit Shaha; Naveed Ahmed; Carina King; Malini Pires; Hassan Haghparast-Bidgoli; Kishwar Azad; Edward Fottrell; Joanna Morrison (BMC, 2023)
Abstract Background Engaging communities is an important component of multisectoral action to address the growing burden of non-communicable diseases (NCDs) in low- and middle-income countries. We conducted research with non-communicable disease stakeholders in Bangladesh to understand how a community-led intervention which was shown to reduce the incidence of type 2 diabetes in rural Bangladesh could be scaled-up. Methods We purposively sampled any actor who could have an interest in the intervention, or that could affect or be affected by the intervention. We interviewed central level stakeholders from donor agencies, national health policy levels, public, non-governmental, and research sectors to identify scale-up mechanisms. We interviewed community health workers, policy makers, and non-governmental stakeholders, to explore the feasibility and acceptability of implementing the suggested mechanisms. We discussed scale-up options in focus groups with community members who had attended a community-led intervention. We iteratively developed our data collection tools based on our analysis and re-interviewed some participants. We analysed the data deductively using a stakeholder analysis framework, and inductively from codes identified in the data. Results Despite interest in addressing NCDs, there was a lack of a clear community engagement strategy at the government level, and most interventions have been implemented by non-governmental organisations. Many felt the Ministry of Health and Family Welfare should lead on community engagement, and NCD screening and referral has been added to the responsibilities of community health workers and health volunteers. Yet there remains a focus on reproductive health and NCD diagnosis and referral instead of prevention at the community level. There is potential to engage health volunteers in community-led interventions, but their present focus on engaging women for reproductive health does not fit with community needs for NCD prevention. Conclusions Research highlighted the need for a preventative community engagement strategy to address NCDs, and the potential to utilise existing cadres to scale-up community-led interventions. It will be important to work with key stakeholders to address gender issues and ensure flexibility and responsiveness to community concerns. We indicate areas for further implementation research to develop scaled-up models of community-led interventions to address NCDs.